Understanding consumer intention to pay by contactless credit cards in Taiwan. (2019) - Wang, Yu-Min; Lin, Wei-Cheng
Contactless payment is a revolutionary innovation in transaction payments. Little is known, however, about what shapes consumers' willingness to use this method. This study investigates the antecedents of consumer intention to pay using contactless credit cards, along with relationships among these antecedents. Based on the technology acceptance model and innovation diffusion theory, eight variables (usefulness, ease of use, perceived behavioural control, compatibility, perceived risk, trust, personal innovativeness, and consumer involvement) are proposed to analyse consumer decisions to pay using contactless credit cards. The model was evaluated using survey data from 246 consumers in Taiwan. The results indicate that compatibility and perceived risk are key determinants of consumers' use intention to pay by contactless credit cards. However, consumers do not appear to consider the main constructs of TAM in their use intention. This study extends the knowledge of consumers' payment-decision making and provides insights into how to promote contactless credit cards.